Synthesis of hybrid nanosorbent CaO incorporated with MgO-SiO2 for enhancement CO2 capture performance and cyclic stability - Mohd Daud, Farah Diana (International Islamic University Malaysia, 2020)
A high magnitude of greenhouse gases, carbon dioxide (CO2) released into the air has been really alarming and contributing to climate disasters of global warming.Many studies reported that calcium oxide (CaO) is stoichiometrically and reversibly react with CO2 used for CO2 removal are not efficient for practical purpose due to sintering which suffer from structural instability, thus reduced capturing (adsorption) capacity and sorbent recyclability .The most important criterion to prevent the sintering and to increase the capturing capacity is to increase the surface area by manipulating CaO at the nano level with uniform distribution. The incorporation CaO with magnesium oxide and silica (MgO-SiO2) as hybrid nanosorbent would be beneficial because MgO and CaO alone have shown high capacity and affinity toward CO2 at ambient (1 atm, 0-25°C), and flue gas (1 atm, 120°C) conditions, which after merging with SiO2 can be substantially enlarged due to the high active surface area and well-developed porosity of the hybrid sorbents. Therefore, the ultimate aim of this work is to synthesis hybrid nanosorbent of CaO incorporated with MgO and SiO2 via coprecipitation. The SiO2 precursor will be produced using the natural source, silica sand through alkali fusion method.The CaO will be incoporated with MgO and SiO2 at different ratio, synthesis temperature and time,catalyst concentration, type of solvent,and calcination temperature.The CO2 capture of hybrid nanosorbent materials will be measured by using a thermogravimetric analyzer (TGA) at multiple cyclic of adsorption and desorption at different temperature.The synthesis nanosorbent is expected to have excellent sintering resistant (MgO) and structural stability (SiO2) which improved sufficiently cyclic adsorption/desorption operations.These findings will then benefit in capturing CO2 whereby designated hybrid nanosorbent materials with optimum properties are reliable and can be fully utilized in the combustion flue gases,power plants, industrial processes and transport.